Karakteristik Fasies Turbidit Formasi Dolokapa Berdasarkan Data Stratigrafi Terukur di Kabupaten Gorontalo Utara - Yulin Podungge (Journal of Applied Geoscience and Engineering, 2026)
The Dolokapa Formation in North Gorontalo is a volcano-sedimentary unit whose sedimentary succession records deep-marine gravity-flow processes. This study aims to identify turbidite facies characteristics and reconstruct the submarine-fan depositional model based on measured stratigraphic sections. Field data were collected from three main observation routes, namely the Dolokapa, Sipatana, and Mooti Rivers, through lithological description, bed-thickness measurement, sedimentary-structure observation, and facies interpretation using the concepts of Bouma, Walker, Mutti, and Petter. The results indicate five facies associations: fining-upward wacke sandstone, coarsening-upward wacke sandstone, interbedded claystone and sandstone, interbedded sandstone and claystone with siltstone intercalation, and interbedded sandstone and claystone with conglomerate intercalation. These facies represent different parts of a submarine fan system, ranging from the upper fan to the channeled and smooth portions of suprafan lobes in the mid fan. The vertical facies succession suggests repeated turbidity-current deposition involving low-density turbidity currents, high-density turbidity currents, and cohesive debris-flow processes. This study refines local facies data of the Dolokapa Formation and supports its interpretation as a deep-marine submarine-fan deposit.